1977
DOI: 10.1029/jb082i026p03694
|View full text |Cite
|
Sign up to set email alerts
|

The effects of subsurface boiling and dilution on the isotopic compositions of Yellowstone thermal waters

Abstract: Studies of isotope hydrology of geothermal systems have generally emphasized deep circulation of meteoric water, demonstrated by constancy of deuterium contents, and an ‘oxygen isotope shift’ to higher oxygen 18 contents produced by water‐rock reactions. However, subsurface boiling (in high‐temperature systems) and dilution may cause deuterium (and oxygen 18) contents of hot spring and recharge waters to difference significantly. By using thermodynamic and isotopic fractionation data for water and steam the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0
3

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(120 citation statements)
references
References 27 publications
(4 reference statements)
6
111
0
3
Order By: Relevance
“…thermometer from Truesdell et al (1977). Error bars for K/Mg and quartz variants are within point size.…”
Section: Tablesmentioning
confidence: 99%
“…thermometer from Truesdell et al (1977). Error bars for K/Mg and quartz variants are within point size.…”
Section: Tablesmentioning
confidence: 99%
“…Studies of the Yellowstone hydrothermal system (Truesdell and Fournier, 1976;Truesdell et al, 1977;Mazor and Thompson, 1982;and Fournier, 1988) have suggested that the thermal water from the various basins originates from the same deep reservoir. This conclusion is based on the similar maximum temperatures determined at depth, similar isotopic composition of the source water, and similar chemistries for certain diagnostic elements of the spring waters.…”
Section: A Trajectories and Manding Curves Of Thermal Water Of The Normentioning
confidence: 99%
“…Truesdell and Fournier (1976) and Fournier (1989) have suggested that the reservoir is located beneath the caldera at a depth of 3-5 km. Truesdell et al (1977) believe that the primary water has a chloride concentration of 310 ppm. Oxygen and hydrogen isotopes have shown that the majority of the thermal water which surfaces in Yellowstone is of meteoric origin (see Craig, 1963, andTruesdell et al, 1977).…”
Section: A Trajectories and Manding Curves Of Thermal Water Of The Normentioning
confidence: 99%
See 2 more Smart Citations